2008 23rd IEEE/ACM International Conference on Automated Software Engineering 2008
DOI: 10.1109/ase.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

MaramaEML: An Integrated Multi-View Business Process Modelling Environment with Tree-Overlays, Zoomable Interfaces and Code Generation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…On the contrary, capture rates of these two species were uncorrelated with fragment size in southeastern Madagascar (Ramanamanjato & Ganzhorn, 2001).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…On the contrary, capture rates of these two species were uncorrelated with fragment size in southeastern Madagascar (Ramanamanjato & Ganzhorn, 2001).…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies also showed that capture rates of Eliurus spp. declined significantly with declining fragment size in western and southeastern Madagascar (Ganzhorn, 2003;Ramanamanjato & Ganzhorn, 2001). Burke and Lehman (2014) found that M. ravelobensis was trapped in even higher numbers near habitat edges (5-50-m distance from edge) compared to the interior of another continuous forest in ANP.…”
Section: Impact Of Fragment Characteristics On Species Abundancementioning
confidence: 99%
“…In the realm of enterprise modeling, layout has been discussed for view-based enterprise engineering [14]. Work on tree-based visualization of EA has resulted in multiple visual notations [15]. The comprehensibility of a diagram in part depends on its layout [16].…”
Section: Introductionmentioning
confidence: 99%
“…From SUDDEN models (1) we developed a set of candidate visual languages using a set of principled approaches (2). We gained user feedback on candidate VLs (3) and then developed a set of meta-models in our Marama visual modelling meta-tool [8] to describe the VL elements and underlying SUDDEN constructs (4). We then developed a visual modelling tool using the Marama metatool, MaramaSUDDEN, including support for import and export of simulated supply chain specifications to a shared semantic web-based ontology (5).…”
Section: Our Approachmentioning
confidence: 99%
“…A key challenge is to make these constructs and models based on them tractable for SME end users. One solution is to provide a suitable domain-specific visual modelling language (DSVL), extracting a simplified view of the underlying meta-model customised to the skills profile of our target end users; and developing an appropriate suite of support tools to assist them [3,4].…”
Section: Introductionmentioning
confidence: 99%